Epigenetics and developmental programming of welfare and production traits in farm animals - Sinclair, Kevin D.; Rutherford, K.M.D.; Wallace, J.M.; Brameld, J.M.; Stöger, Reinhard; Alberio, Ramiro; Sweetman, Dylan; Gardner, David S.; Perry, V.E.A.; Adam, C.L.; Ashworth, C.J.; Robinson, J.E.; et al. (CSIRO Publishing, 2016)
The concept that postnatal health and development can be influenced by events that occur in utero originated from epidemiological studies in humans supported by numerous mechanistic (including epigenetic) studies in a variety of model species. Referred to as the ‘developmental origins of health and disease’ or ‘DOHaD’ hypothesis, the primary focus of large-animal studies until quite recently had been biomedical. Attention has since turned towards traits of commercial importance in farm animals. Herein we review the evidence that prenatal risk factors, including suboptimal parental nutrition, gestational stress, exposure to environmental chemicals and advanced breeding technologies, can determine traits such as postnatal growth, feed efficiency, milk yield, carcass composition, animal welfare and reproductive potential. We consider the role of epigenetic and cytoplasmic mechanisms of inheritance, and discuss implications for livestock production and future research endeavours. We conclude that although the concept is proven for several traits, issues relating to effect size, and hence commercial importance, remain. Studies have also invariably been conducted under controlled experimental conditions, frequently assessing single risk factors, thereby limiting their translational value for livestock production. We propose concerted international research efforts that consider multiple, concurrent stressors to better represent effects of contemporary animal production systems.